Lothian - Geddes, Jane; Gow, Ian 1953-; MacKechnie, Aonghus; Tabraham, Chris; McWilliam, Colin 1928-1989 (Yale University Press, 2024)
This is the first fully revised and expanded guide to the buildings of Lothian since Colin McWilliam's pioneering volume of 1978, with new colour photography, maps and plans to accompany the unrivalled coverage of the area. Lothian surrounds the capital city of Edinburgh, which has done much to influence the character of its buildings. Among these are some important medieval relics, including the internationally-famous Rosslyn Chapel, the royal Renaissance palace at Linlithgow and the ruins of great castles and tower houses. Among major country houses, none are more splendid than Hopetoun and the ducal seat of Dalkeith Palace but Lothian also has the extraordinarily well-preserved Newhailes and mighty Gosford House. This is also an area of picturesque small towns and resorts along the Firth of Forth with outstanding villas for the Edwardian elite, and rural villages of unspoiled character, preserving remains of their agricultural heritage. The industrial legacy is important, including not only one of the most complete collieries in Scotland but also the world-famous Forth Rail Bridge. This volume is an essential reference for visitors and residents alike
Includes bibliographical references and indexes
Keywords: Architektur; Lothian Region; Architecture / Scotland / Lothian; Architecture / Scotland / Lothian / Guidebooks; Buildings / Scotland / Lothian; Buildings / Scotland / Lothian / Guidebooks; Architecture - Écosse - Lothian; Architecture - Écosse - Lothian - Guides; Constructions - Écosse - Lothian; Constructions - Écosse - Lothian - Guides; Lothian (Scotland) / Guidebooks; Lothian (Écosse) - Guides; Kunstführer